Challenging the cult of normalcy: Arts education and transdisciplinary practices. Issue 3 (1st December 2017) - Tobias-Green, Karen
I am interested in art education as a transdisciplinary practice that embraces a variety of mediums and world-views and in how, through transdisciplinarity, art education challenges the cult of normalcy. The normalization of the individual is a limiting, destructive and pedagogically unsound basis from which to pursue any kind of education and particularly one where the contribution of the individual is as central as it is in art education. The adoption of a transdisciplinary practice can be liberating on a personal, an artistic and a pedagogic level.